Dinámica de funciones de variable compleja en el Disco (2019)
In this work we study the holomorphic functions of the unit disk and its properties related to the dynamics in points inside and the edge of the disk. This study will be done using the pseudo hyperbolic metric, in particular we make use of the pseudo hyperbolic balls. We define and study angular limits and the relationship between different results about the dynamics of these iterated